Effect of the size reduction on the bulk tensile and double cantilever beam specimens used in cohesive zone models - Costa, M. (2016)
Cohesive zone elements used in finite element analysis are a reliable way to design and predict the behaviour of the joint. The characterisation of the traction separation law used in these models is done using tensile and fracture tests, and the parameters of such laws depend on humidity and temperature. Water diffusion tests are therefore necessary, which are dependent on specimen geometry, meaning a bigger specimen takes longer to fully saturate. To solve this problem and increase the efficiency of the ageing process, smaller tensile bulk and double cantilever beam (DCB) specimens are necessary. Another advantage of smaller DCB specimens is that they can be tested in smaller high-temperature chambers, where normal DCB specimens do not fit. Smaller geometries of the bulk tensile and DCB tests are analysed, and a proposed geometry for each test is shown to produce very satisfactory results, validating the use of these specimens.